Moving beyond the language–Visualizing chemical concepts through one’s own creative expression - Adbo, Karina; AAkesson-Nilsson, Gunilla (Frontiers in Education, 2022)
The results presented here derive from a study exploring students’ interpretations of a chemical content in the form of physical constructions of atomic nuclei. The aim of the study was to explore this method as a tool for problem-solving and as a way of expressing interpretations of concepts such as atomic nuclei, nucleons, and isotopes. Playdough was chosen as the means for expression, since it provided the students with the task of choosing the number, form, size, shape, and distance of particles. Three levels of analysis as presented by Hedegaard were performed and framed within the theories of models and analogy. Results show that students’ choices gave rise to a series of atomic nuclei that varied depending on what aspect the students focused on at the time, leading to nuclei that are seen as flat, round, square, circular, linear, linear-curved, triangular, doughnut-shaped, and star-shaped. It was not uncommon for one student to create more than two shapes. Results show the importance of visualisations in science and add to the discussion concerning the multitude of atomic models used in teaching. The method was indeed a beneficial tool both for students, who could explore the composition of atomic nuclei and isotopes, and for teachers, who could connect their teaching to students’ interpretations of scientific content since the method brings a new level of detail to discussions.